2011
DOI: 10.1016/j.juro.2011.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Followup of Unilateral Renal Function After Laparoscopic Partial Nephrectomy

Abstract: Function of the kidney undergoing laparoscopic partial nephrectomy progressively recovers after a significant decrease immediately after surgery. Although recovery differs according to patient age, comorbidities and tumor size, factors that independently predicted the postoperative glomerular filtration rate decrease were the renal parenchymal volume reduction and pelvicalyceal system repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…[4][5] The main predictors of new baseline glomerular function rate (GFR) after PN are the quality and quantity of preserved parenchymal mass, with intraoperative ischemia playing a secondary role presuming that hypothermia or limited warm ischemia has been applied. [6][7][8][9][10][11][12][13][14] The quality of the preoperative kidney is predominantly nonmodifiable and dependent on age and pre-existing comorbidities. In traditional PN, the tumor is excised with a small rim of normal parenchyma and reconstruction is performed in a manner to preserve vascularity to as much of the remaining parenchyma as possible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5] The main predictors of new baseline glomerular function rate (GFR) after PN are the quality and quantity of preserved parenchymal mass, with intraoperative ischemia playing a secondary role presuming that hypothermia or limited warm ischemia has been applied. [6][7][8][9][10][11][12][13][14] The quality of the preoperative kidney is predominantly nonmodifiable and dependent on age and pre-existing comorbidities. In traditional PN, the tumor is excised with a small rim of normal parenchyma and reconstruction is performed in a manner to preserve vascularity to as much of the remaining parenchyma as possible.…”
Section: Resultsmentioning
confidence: 99%
“…14 Most studies in this field have used computed tomography (CT) scans to estimate preoperative and postoperative vascularized parenchymal volumes, with some using a freehand scripting approach and others automated analysis based on sophisticated software to differentiate densities within the studies. [6][7][8][9][10][11][12][13] Comparative analyses for these 2 techniques are not available in the setting of PN.…”
Section: Resultsmentioning
confidence: 99%
“…Current literature has not concluded to the most important factor for the renal function decline after PN and the contribution of WI to the postoperative renal function has not been well documented (17). Some investigators advocated that the parenchymal mass preservation was stronger correlated to the functional recovery in comparison to the WI (4,19). The current prospective study aimed in distinguishing the impact of parenchymal loss from the WI effect on the operated kidney.…”
Section: Figure 5: the Graph Shows The Mean Decline Of Both P-drf Andmentioning
confidence: 92%
“…Current evidence showed that the length of the warm ischemia time (WIT) and the subsequent reperfusion injury may result in permanent renal damage (1,2). Moreover, the resection of the renal tumour and the suturing of the parenchyma resulted in additional reduction of the functional renal tissue (3,4). Thus, two mechanisms of renal function damage during PN could be proposed.…”
Section: Introductionmentioning
confidence: 99%
“…DTPA renal scintigraphy was performed according to the standardized protocol of our institution [6]. Because total and operated-side renal function are reported to significantly decrease for the first 3 months after PN and to stabilize thereafter [15], preoperative and postoperative 3-month and 1-year total and split renal function were measured using DTPA renal scintigraphy. Postoperative decrements in GFR were calculated on the operated side, the contralateral side, and in total at 3 months and 1 year postoperatively using the formula: decrements in GFR (ΔGFR) = preoperative GFR − postoperative GFR.…”
Section: Methodsmentioning
confidence: 99%